Essentials of MMPI-2 Assessment - Nichols, David S. (Hoboken, New Jersey : Wiley, 2011)
'The Minnesota Multiphasic Personality Inventory, Second Edition is used by a broad range of clinicians to assist with the diagnosis of mental disorders and the selection of appropriate treatment methods. To use it properly, professionals need an authoritative source for use of this test. This thoroughly updated and revised second edition of Essentials of MMPI-2 Assessment provides that resource. In addition to comprehensive updates to the research and literature throughout, the new edition will include information on other versions of the test, including the MMPI-2 RC and the MMPI-2-RF. Clinical and school psychologists are provided with information on administering, interpreting, and scoring this most widely used test for assessing personality'--
Includes bibliographical references and index.
Keywords: Minnesota Mutiphasic Personality Inventory; PSYCHOLOGY / Clinical Psychology